Pregnancies following Protocols for Repetitive Synchronization of Ovulation in Primiparous Buffaloes in Different Seasons - Giorgio A. Presicce; Domenico Vistocco; Massimo Capuano; Luigi Navas; Angela Salzano; Giovanna Bifulco; Giuseppe Campanile; Gianluca Neglia (Veterinary Sciences, 2022)
Primiparous buffaloes were tested in two periods of the year characterized, by either low or high reproductive efficiency. They were subjected to two protocols for synchronization of ovulation: (i) Ovsynch (OV) and (ii) progesterone based (P4) treatment. After calving, the animals underwent a series of four cycles of re-synchronization protocols. The season did not affect pregnancy rates when the results of the two treatments were pooled together with regard to the first synchronization protocol, followed by AI. Pregnancy rates were similar during the low breeding season (50.3% vs. 57.4% in OV and P4, respectively), but different during the high breeding season (50.4% vs. 67.7% in OV and P4, respectively; p = 0.000). Logistic regression confirmed a significant effect of treatment and season interaction on pregnancy (p = 0.003). Following re-synchronization, a treatment by season interaction was detected during the low breeding season (odds ratio = 2.233), in favor of P4. Finally, a survival analysis showed a better response of animals subjected to P4 treatment from the second AI onward. In conclusion, the pooled data of pregnancy rates from both treatments between seasons are not different following AIs. Better results, though, were obtained from the implementation of P4 treatment, and are recorded in a season-fashioned mode when the comparison is made following first or cumulative AIs.